2017
DOI: 10.1109/tnet.2016.2574563
|View full text |Cite
|
Sign up to set email alerts
|

Optimally Approximating the Coverage Lifetime of Wireless Sensor Networks

Abstract: Abstract-We consider the problem of maximizing the lifetime of coverage (MLCP) of targets in a wireless sensor network with battery-limited sensors. We first show that the MLCP cannot be approximated within a factor less than ln n by any polynomial time algorithm, where n is the number of targets. This provides closure to the long-standing open problem of showing optimality of previously known ln n approximation algorithms. We also derive a new ln n approximation to the MLCP by showing a ln n approximation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Pananjady et al focused on the problem of energy efficiency in sensor networks, and aimed to solve the issue of maximizing the lifetime of coverage of targets in a wireless sensor network with battery-limited sensors. Extensive simulation experiments prove the effectiveness of the proposed algorithm [18].…”
Section: Related Workmentioning
confidence: 76%
“…Pananjady et al focused on the problem of energy efficiency in sensor networks, and aimed to solve the issue of maximizing the lifetime of coverage of targets in a wireless sensor network with battery-limited sensors. Extensive simulation experiments prove the effectiveness of the proposed algorithm [18].…”
Section: Related Workmentioning
confidence: 76%
“…YOLO (you only look once) [ 48 , 49 , 50 , 51 ] is a real-time object detector based on convolutional neural networks introduced by Redmon et al After some time, Joseph Redmon and Ali Farhadi published YOLO v2 [ 52 ], a new version with improved performance and speed. The most recent version is YOLO v3 [ 53 ], which was proposed by Joseph Redmon and Ali Farhadi to enhance speed and accuracy by increasing the number of layers in the design.…”
Section: Methodsmentioning
confidence: 99%
“…This solution, however, has been shown to be NP-complete. As a result, authors in [27][28][29] have suggested a centralised heuristic method to achieve coverage. Cover sets are generated by this method, which aid in the monitoring of all targets.…”
Section: Related Workmentioning
confidence: 99%